Human skeletal muscle is refractory to the anabolic effects of leucine during the postprandial muscle-full period in older men - Mitchell, W. Kyle; Phillips, Bethan E.; Hill, Ian; Greenhaff, Paul L.; Lund, Jonathan N.; Williams, John P.; Rankin, Debbie; Wilkinson, Daniel J.; Smith, Kenneth; Atherton, Philip J. (Portland Press, 2017)
Leucine modulates muscle protein synthesis (MPS), with potential to facilitate accrual/maintenance of muscle mass. Animal models suggest that leucine boluses shortly after meals may prolong MPS and delay onset of a “muscle-full” state. However, the effects of nutrient “top-ups” in humans, and particularly older adults where deficits exist, have not been explored. We determined the effects of a leucine top-up after essential amino acid (EAA) feeding on anabolic signaling, MPS, and muscle energy metabolism in older men. During 13C6-phenylalanine infusion, 16 men (∼70 years) consumed 15 g of EAA with (n=8, FED + LEU) or without (n=8, FED) 3 g of leucine top-up 90 min later. Repeated blood and muscle sampling permitted measurement of fasting and postprandial plasma EAA, insulin, anabolic signaling including mTOR complex 1 (mTORC1) substrates, cellular ATP and phosphorylocreatine, and MPS. Oral EAA achieved rapid insulinemia (12.5 iU·ml−1 25 min post-feed), essential aminoacidemia (3000 μM, 45–65 min post-feed), and activation of mTORC1 signaling. Leucine top-up prolonged plasma EAA (2800 μM, 135 min) and leucine availability (1050 μM, 135 min post-feed). Fasting FSRs of 0.046 and 0.056%·h-1 (FED and FED + LEU respectively) increased to 0.085 and 0.085%·h-1 90–180 min post-feed and returned to basal rates after 180 min in both groups. Phosphorylation of mTORC1 substrates returned to fasting levels 240 min post-feed in both groups. Feeding had limited effect on muscle elongation factor 2 (eEF2) phosphorylation. We demonstrate the refractoriness of muscle to nutrient-led anabolic stimulation in the postprandial period; thus, leucine supplements should be taken outside of meals, or with meals containing suboptimal protein in terms of either amount or EAA composition.